1971
DOI: 10.1017/s002185960002565x
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship of some components of forage quality

Abstract: To produce forage crop varieties of improved quality, the plant breeder must consider both the content of the quality components and their interrelationships.The methods used to examine the interrelationships involve simple correlations and path analyses. In the path analyses a dependent variate is specified which is completely and additively determined by a number of independent variates. The amount of variation present in the dependent variate accounted for by variation in each of the independent variates is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…(1994) that selection for high WSC concentration has not been at the expense of CP concentration. The negative relationship between WSC and CP reported previously (Dent & Aldrich 1963; Thompson & Rogers 1971; Stewart et al . 2009) was suggested by Radojevic et al .…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…(1994) that selection for high WSC concentration has not been at the expense of CP concentration. The negative relationship between WSC and CP reported previously (Dent & Aldrich 1963; Thompson & Rogers 1971; Stewart et al . 2009) was suggested by Radojevic et al .…”
Section: Discussionmentioning
confidence: 48%
“…The similar results of these two studies support the conclusion of Radojevic et al (1994) that selection for high WSC concentration has not been at the expense of CP concentration. The negative relationship between WSC and CP reported previously (Dent & Aldrich 1963;Thompson & Rogers 1971;Stewart et al 2009) was suggested by Radojevic et al (1994) to be more likely a result of environmental, rather than genetic factors. While CP concentration did not vary between cultivars, lower fibre concentrations were measured in both the high sugar cultivars compared to the control.…”
Section: Resultsmentioning
confidence: 62%
“…It is commonly found that WSC and CP are strongly negatively related both in individual plants (Vose and Breese, 1964;Valentine and Charles, 1979;Bugge, 1978) and in swards (Dent and Aldrich, 1963;Thompson and Rogers, 1971 and Grimes et al, 1967). This would suggest a strict limit on the proportion of cell content to cell wall in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, WSC appears to play a key role in feeding value but is necessarily interrelated with other herbage quality components such as DMD and CP. Some of these relationships were investigated in detail in timothy by Thompson and Rogers (1971) and to some extent in perennial ryegrass by Dent and Aldrich (1963). Relationships between WSC content and herbage production are not well documented, although WSC is necessarily linked to growth as a store of energy and as an osmoticum promoting water uptake during cell, and hence leaf, expansion.…”
Section: Introductionmentioning
confidence: 99%